Economic Bulletin : January 2004 : Volume 6 / Department of Economic Studies - UiTM, Department of Economic Studies (Faculty of Business Management, UiTM, 2004)
The main objective of this journal is to provide the much needed intellectual platform to all economic lecturers of UiTM. This platform is an excellent avenue to publish their research works based on economics and at the same time provide a generous space to those who want to probe economic issues that are pertinent to the economy and the university. In a small way this journal (partially refereed) has fulfilled this role over the years and we will continue to do so in the future. As usual, the Editorial Board holds the tradition of publishing at least five articles on conventional economics and one article on Islamic economics. The Editorial Board thanks the present Dean of Faculty of Business Management, Shah Alam, for providing the impetus and the required financing to publish this much awaited Volume 6, Economic Bulletin of the faculty.